Voluntary sustainability disclosure, revenue, and shareholders wealth- a perspective from Singaporean companies - Khaveh, Amir; Nikhashemi, Seyed Rajab; Yousefi, Abdolaziz; Haque, A. K. M. Ahasanul (Society of Business and Management Dynamics, 2012)
There is an unprecedented growth among wide range of stakeholder’s attention to environmental and social performance, and disclosure by companies. People within a community are worried about natural resources, air and water pollution, as well as low income-tier group of the community. Companies started to perform in a way to minimize their negative and adverse impact on natural scarce resources, and practice some social-friendly activities in order to either build a shared value for long term purpose, and to gain customers and shareholders attention for short term purposes. Since environmental and social issues are associated with peoples’ right and public law, thus some governments have legislated certain rules and regulations and also have made CSR disclosure as a mandatory practice for public listed firms. But CSR disclosure is still optional in most of countries. Environmental and social performance and disclosure in Singapore are not mandatory. So Singaporean public listed companies perform and disclose their CSR activities voluntarily.. Findings of this research show that there is a positive and significant relationship between environmental and social performance disclosure as well as revenue. This research investigated the relationship between environmental and social disclosure and shareholders wealth in Singapore; meanwhile it has found that there is a positive and considerable relationship between sustainability reporting and amount of paid dividend and share price as well.